Ergonomics study in the stress level among Electronics Assembly Line Workers - Kamarulzaman, Mahmad Khairai; Muhammad Nubli, Abdul Wahab; Ezrin Hani, Sukadarin (2019)
Human and cognitive ergonomics become one of essential elements in industrial field nowadays due to employer concern on physical, spiritual and emotional of their workers. The need of industrial today required operator’s cognitive functions with less manual human control but in reality human judgement cannot be eliminate as there are various task that only can be perform by human. The objective of this study is to investigate the level of stress among Muslim electronics assembly line workers in electronic factories in Malaysia. The method used in this study is a survey questionnaire. The study is to compare the stress level between male and female, different ages of worker, years of working experience and task deliver in the plant to perform their duty and contribute to company. The tool administered is DASS 42 questions which distributed to the 360 worker from different level which is staffs and operators. Based on it, emWavePro device are used to test workers biofeedback performance in order to determine target persons for stress management module implementation. Workers performances in terms of productivity are measure after complete module implementation. The result may shows that workers that undergo this programed as a subjects improve their work performance by increasing productivity. Workers may came to work with positive attitude that impact positive environment to the plant. Using DASS, 319 of electronics assembly line workers are evaluated and from that 18 workers are identified with extremely severe of depression, anxiety and stress. From 18 workers, 61.1% are come from age between 19 and 29 years old with working experience less than 5 years. These 18 workers had potential to influence others that can disturb positive environment on the plant and change it to negative environment. Cognitive ergonomics is one of important elements to be focus as it impact workers performance every day. Not only physical, spiritual and emotional of the workers also contribute to the plant achievement in general.